Tracing The Cinematic Female Gaze Through Textual Film Analysis of Something Useful (2017) - Beril Uğuz (Art Vision, 2024)
It is essential to investigate what constitutes the cinematic female gaze to discuss the potential differentiation in films directed by female directors from traditional cinema. The concept of the female gaze, frequently brought to the forefront in recent years, remains a subject of ongoing academic research. This study aims to contribute to the definition of the cinematic female gaze by examining how it is constructed in cinema. For this purpose, the film Something Useful (2017) directed by Pelin Esmer, was selected and analyzed using a textual film analysis method that prioritizes visual, auditory, and thematic elements. According to the findings, the look, sound, perspective, emotions, thoughts, feelings, and inner state of the female character in Something Useful, briefly the qualities that nourish her subjectivity—are conveyed to the audience or are made to be felt by the audience, through various cinematographic, editing, and mise-en-scène tools. The subjectivity of woman is also thematically emphasized by her interaction with social life, relationships between women and a curiosity to understand and define life. The film diverges from mainstream cinema codes by having process-orientedness and passionate detachment. When these features are considered along with other studies in the literature, it becomes possible to propose a potential definition for the construction of the cinematic female gaze.